Extraction of Tsunami Damaged Areas Due to the 2010 Chile Earthquake Using Optical and SAR Data of ALOS - Jaya, Ni Made Pertiwi; Miura, Fusanori (International Journal of Environment and Geosciences; Vol 2 No 2 (2018)DO - 10.24843/ijeg.2018.v02.i02.p02, 2018)
Information about damage areas is important due to the large-scale disasters worldwide. In the last decade, both optical and SAR remote sensing were applied in many disaster researches, such as tsunami damage detection. In this study, the ALOS AVNIR-2 and PALSAR images are used to extract the damaged areas caused by the 2010 Chile earthquake. In the processing of ALOS/AVNIR-2, the inundation area was estimated based on the NDVI calculation and classification. Furthermore, damaged areas of the ALOS/PALSAR are extracted by integrating the AVNIR-2 image for water mask and the DEM image for elevation mask. The damaged area result of AVNIR-2 is 8.91 Km2 and for the PALSAR is 8.72 Km2 that is along the coastal areas. The image results showed a good agreement and corresponding area according to the institutional map of the inundation area. Future study in another area is needed in order to strengthen the processing method.